Rendición de cuentas y participación ciudadana en el distrito de Contamana 2025 - Dos Santos Ramirez, Alices Arlenit (2025)
The study aimed to determine the relationship between accountability and citizen participation in the district of Contamana, 2025. This was a basic research study, with a quantitative approach, a descriptive correlational level, and a non-experimental design. The sample consisted of 379 residents, who were surveyed as a data collection instrument. The results showed that accountability in the district was rated as average, with a score of 32%. This is explained by the fact that the majority of residents believe that the municipality almost always reports the results of its management in a clear and understandable manner. However, only occasionally is the municipality's financial and budgetary information published in a manner accessible to citizens. Regarding citizen participation, this was also rated as average, with a score of 33%. Respondents indicated that the municipality occasionally provides useful and easily accessible information. However, they emphasize that official documents and communications are almost always presented in clear and understandable language. Finally, it is concluded that there is a high positive correlation (r = 0.723) between accountability and citizen participation, with a level of statistical significance (sig. = 0.000 < 0.01). Consequently, the alternative hypothesis is accepted and it is established that both variables are significantly related.